Pengaruh Promosi Terhadap Brand Awareness di Aplikasi Zalora Indonesia - Dewi Kurniaty; Marisa Hardina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to investigate the effect of promotions on brand awareness in the ZALORA Indonesia app. The research method used is quantitative. Data were collected through a questionnaire distributed to 140 respondents who are aware of ZALORA Indonesia's promotions on social media. This study applies a convenience sampling method, and the obtained data were analyzed using the Statistical Package for the Social Sciences (SPSS). Data testing was conducted through Descriptive Tests, Validity Tests, Reliability Tests, and Hypothesis Testing. The analysis results indicate that promotions have a significant effect on brand awareness in the ZALORA Indonesia app. The implications of this research suggest that ZALORA Indonesia should implement promotions in a more structured and scheduled manner. Additionally, ZALORA Indonesia needs to continually update all promotional content across all existing social media platforms to enhance consumer awareness of ZALORA Indonesia. This study recommends that ZALORA Indonesia continue to disseminate engaging and up-to-date information to facilitate better reception by consumers.